Foavedur mass media for children and modifyin Their behaviour from point of their parents view: Foavedur mass media for children and modifyin Their behaviour from point of their parents view (Journal of the College of Education for Women, 2019)
Abstract:The research aimed to know favoured mass media for children andmodifying their behaviour ,the child became aquires the information frommass media that he exposure them without any guidance , where upon thequidance proqrammes becomes real danger whereas qet out their civilstyle and converting to deadly poisons,and because of little study for thissupject the two researchers opined to perform astudy to know the favouredmass media to the children and what are the mass media that modify theirbehavior according to ther parent points of view ,after propring the researchmeasurement and the suilable statical methods it has shown that there aremass media affect in children behavior ,they are story in first class ,then t.v.and finally computer but the favoured mass media more than others is t.v.and then story and finlly the computer and the story affect positively inmodifying chidren behaviour , the two researcher recommended that it isnecessery for children parents to observes mass and they suggested toperform evaluation study for reading audible and visual mass media in whatthey present special media methods of children .